Celiac Disease: Fallacies and Facts. (17th June 2021) - Silvester, Jocelyn A.; Therrien, Amelie; Kelly, Ciaran P.
Abstract : Our understanding of the pathophysiology of celiac disease has progressed greatly over the past 25 years; however, some fallacies about the clinical characteristics and management persist. Worldwide epidemiologic data are now available showing that celiac disease is ubiquitous. An elevated body mass index is common at the time of the diagnosis. The gluten-free diet (GFD) is an imperfect treatment for celiac disease; not all individuals show a response. This diet is widely used by people without celiac disease, and symptomatic improvement on a GFD is not sufficient for diagnosis. Finally, the GFD is burdensome, difficult to achieve, and thus has an incomplete efficacy, opening exciting opportunities for novel, nondietary treatments.